Pengaruh Digital Marketing, Brand Image Dan Influencer Marketing Pada Keputusan Pembelian Scarlett Whitening Di Shopee - Nurul Nanda Sadevia; Ida Bagus Eka Artika; Satriawan (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2023)
This study aims to determine the significance of the simultaneous and partial influence of digital marketing, brand image, and influencer marketing variables on the purchase decision of Scralett Whitening at Shopee, as well as to determine the variables that have a dominant influence. The data collection technique used a questionnaire, and the data analysis used multiple linear regression analysis. The results of the study obtained multiple linear regression equations showing (Y = 0.011 + 0.444X1 + 0.313X2 + 0.166X3 + e) ​​it can be concluded that partially, digital marketing and brand image variables have a positive and significant effect on purchasing decisions on Scarlett Whitening products at Shopee while the influencer marketing variable has no significant effect on the decision to purchase Scarlett Whitening products at Shopee. Simultaneously, digital marketing, brand image and influencer marketing variables have a positive and significant effect on purchasing decisions for Scarlett Whitening products at Shopee. Based on the results of this study, it shows that people who use Scarlett Whitening products are not influenced by influencer marketing but look at digital marketing and brand image. So company management should always maintain digital marketing and brand image to increase consumer interest in using Scarlett Whitening products.